Genomic Investigation and Comparative Analysis of European High-Risk Clone of Acinetobacter baumannii ST2 - David Hummel; Janos Juhasz; Katalin Kamotsay; Katalin Kristof; Basil Britto Xavier; Sien De Koster; Dora Szabo; Bela Kocsis (Microorganisms)
Multidrug-resistant Acinetobacter baumannii is a major concern in healthcare institutions worldwide. Several reports described the dissemination of A. baumannii high-risk clones that are responsible for a high number of difficult-to-treat infections. In our study, 19 multidrug-resistant A. baumannii strains from Budapest, Hungary, were investigated based on whole-genome sequencing (WGS). The obtained results were analysed together with data from 433 strains of A. baumannii from the Pathogenwatch database. WGS analysis of 19 A. baumannii strains detected that 12 belonged to ST2 and seven belonged to ST636. Among ST2 strains, 11 out of 12 carried either blaOXA-23 or blaOXA-58 genes; however, all strains of ST636 uniformly carried blaOXA-72 gene. All strains of ST2 and ST636 carried blaOXA-66 and blaADC-25 genes. Based on core genome multilocus sequence typing (cgMLST), 10 strains of ST2 belonged to cgMLST906, one strain to cgMLST458, and one strain to cgMLST1320; by contrast, all strains of ST636 belonged to cgMLST1178. Certain virulence determinants were present in all strains of both ST2 and ST636, namely, Ata, Bap, BfmRS, T2SS and PNAG. Interestingly, OmpA was present in all strains of ST2, but it was absent in all strains of ST636. Comparative analysis of 19 strains of this study and the collection of 433 isolates from Pathogenwatch database, proved a diverse clonal distribution of high-risk A. baumannii clones in Europe. The major clone in Europe is ST2, which is present all over the continent. However, ST636 has been mainly reported in Eastern Europe. Interestingly, cgMLSTs of ST2 correspond to the production of different beta-lactamases, namely, OXA-82 in cgMLST116, OXA-72 in cgMLST506, and cgMLST556, PER-1 in cgMLST456 and cgMLST1041. Our study demonstrates that the ST2 high-risk clone of A. baumannii is the most widespread in Europe; however, based on cgMLST analysis, a detailed detection of beta-lactamase production can be determined.